THE MECHANISM OF THE INTENSIFICATION OF UKRAINIAN INTEGRATION INTO THE EUROPEAN UNION ON THE BASIS OF INTELLECTUAL ELEMENT - Olena Kocherhina (Izdevnieciba "Baltija Publishing", 2018)
The article analysed the current state of the Ukrainian intellectual potential with the purpose of further intensification of the relations between our country and the European Union. The dynamics of Ukrainian migrant workers of different spheres of activities was presented. The Ukrainian labour migrants by their country of residence were discussed. However, the advantages of Ukraine as the source of scientific labour force were provided in order to develop the interaction between Ukraine and the EU.